a) \(\overrightarrow a = \overrightarrow {BA} + \overrightarrow {BC} + \overrightarrow {BB'} = \overrightarrow {BD'} \)
\(|\overrightarrow a | = |\overrightarrow {BD'} | = \sqrt {B{D^2} + D{D^2}} = \sqrt {B{A^2} + B{C^2} + D{D^2}} = \sqrt {1 + 1 + 1} = \sqrt 3 \)
b) \(\overrightarrow b = \overrightarrow {BC} - \overrightarrow {BA} + \overrightarrow {C'A} = \overrightarrow {BC} + \overrightarrow {AB} + \overrightarrow {C'A} = \overrightarrow {CC'} \)
\(|\overrightarrow b | = |\overrightarrow {CC'} | = 1\)
Đúng 0
Bình luận (0)